Metal foil with long resin layer and production method of the same
The metal foil with a long resin layer, featuring a tetrafluoroethylene polymer and optimized processing, addresses the challenges of adhesion and mechanical stability in printed wiring boards, achieving excellent performance in both electrical and mechanical aspects.
Patent Information
- Application Number
- JP2023147783
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
Existing printed wiring boards and laminates face challenges in maintaining adhesion between conductive and insulating layers, while also preventing wrinkles and warping, especially when treated as long bodies like rolls.
A metal foil with a long resin layer containing a tetrafluoroethylene polymer, where the resin layer is optimized with specific thickness ratios, surface roughness values, and processing methods to ensure excellent adhesion and prevent mechanical distortions.
The metal foil with a long resin layer achieves excellent adhesion to conductive layers, low transmission loss in high-frequency regions, and is resistant to wrinkles and warping, making it suitable for use in printed wiring boards and other electronic applications.
Abstract
Description
[Technical field]
[0001] The present invention relates to a long resin-layered metal foil having a resin layer containing a tetrafluoroethylene-based polymer, and a method for producing the same. [Background technology]
[0002] In recent years, in order to cope with the increasing speed and frequency of mobile communication devices such as mobile phones, materials with high thermal conductivity, low linear expansion coefficient, low dielectric constant and low dielectric loss tangent are required for printed circuit boards of communication devices, and tetrafluoroethylene-based polymers with low dielectric constant and low dielectric loss tangent have attracted attention. In addition, with the increasing density of printed wiring boards, there is a demand for printed wiring boards with excellent adhesion between the conductive layer and the insulating layer, suppressing peeling of the fine conductive pattern from the insulating layer, and excellent circuit formation properties. Patent Document 1 proposes a printed wiring board having a polyimide base film with insulating properties and specific surface properties, and a conductive layer on at least one surface of the polyimide base film. Patent Document 2 proposes a laminate in which a metal layer is directly laminated on the surface of a resin layer containing a fluorine-based resin, and the adhesive strength between the resin layer and the metal layer and the surface roughness Sq of the metal layer are within specific ranges. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2016 / 104420 [Patent Document 2] International Publication No. 2023 / 032958 Summary of the Invention [Problem to be solved by the invention]
[0004] The configurations disclosed in Patent Documents 1 and 2 are both aimed at improving the adhesion between the conductive layer (metal layer) and the insulating layer. On the other hand, from the viewpoint of improving the yield and quality of the product, it is required to suppress the occurrence of wrinkles and warping when the printed wiring board or laminate is handled as a long body, for example, as a roll-shaped long body. The present inventors have determined that, in a long piece of metal foil with a resin layer, the thickness of the resin layer containing a tetrafluoroethylene-based polymer is a predetermined ratio to the thickness of the entire metal foil with a resin layer, and that the root mean square height Rq value and the ten-point average roughness Rz at a predetermined position in the short direction on the surface of the resin layer on the side not in contact with the metal foil are jis It has been found that by controlling at least one of the values within a predetermined range, the occurrence of wrinkles and warping can be suppressed. The inventors have also found that when a resin-layered metal foil having such a resin layer is formed by, preferably, applying an aqueous dispersion containing a predetermined concentration of tetrafluoroethylene-based polymer particles in a specific particle size range to a base layer and baking the resulting film, the surface properties that affect physical properties such as adhesion to the conductive layer can be controlled, and the film has excellent physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric tangent) based on the tetrafluoroethylene-based polymer, low transmission loss even in the high frequency range, and furthermore, the occurrence of wrinkles and warping can be suppressed. This finding led to the present invention. An object of the present invention is to provide a long resin-layered metal foil which includes a resin layer containing a tetrafluoroethylene-based polymer, has excellent adhesion to a conductive layer, has low transmission loss in the high frequency range, and is furthermore suppressed in the occurrence of wrinkles and warping, and a method for producing the same. [Means for solving the problem]
[0005] The present invention has the following aspects. [1] A long resin-layered metal foil having, in that order, a metal foil and a resin layer containing a molten sintered body of tetrafluoroethylene-based polymer particles, wherein the ratio of the thickness of the resin layer to the overall thickness of the long resin-layered metal foil is less than 50%, and when the resin layer is divided in the short direction (TD direction) at intervals of 200 mm, the root-mean-square height Rq value (end Rq value) of the TD direction end and the root-mean-square height Rq value (center Rq value) of the TD direction center on the surface of the resin layer not in contact with the metal foil are each less than 0.5 μm, and the ratio of the end Rq value to the center Rq value is in the range of 1±0.5. [2] The ten-point average roughness Rz of the end portion in the TD direction of the surface of the resin layer not in contact with the metal foil jis Value (end Rz jis value), and the ten-point average roughness Rz jis Value (center Rz jis value) are less than 1.5 μm, and the central Rz jis Edge Rz for value jis The long resin-coated metal foil of [1], wherein the ratio of the values is within the range of 1±0.5. [3] The tetrafluoroethylene-based polymer contains, in this order, more than 97.5 mol % and less than 99.5 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), and the carbonyl group-containing group is 1×10 6 or a polymer having 100 or more per unit, or a polymer containing 90 mol% or more but less than 97.5 mol% and more than 2.5 mol% but not more than 10 mol% of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), respectively, in that order, and the number of carbonyl group-containing groups is 1×10 6 The long resin-coated metal foil of [1] or [2], which is a polymer having less than 100 particles per piece. [4] The long resin-layered metal foil according to any one of [1] to [3], wherein the ratio of the thickness of the resin layer to the entire thickness of the long resin-layered metal foil is 35 to 48%. [5] The long resin layer-attached metal foil according to any one of [1] to [4], wherein the thickness of the metal foil is 5 μm or more and 50 μm or less. [6] A method for producing a long resin-layered metal foil according to any one of [1] to [5], comprising coating a metal foil with a dispersion containing 100 parts by mass of tetrafluoroethylene-based polymer particles having an average particle size of 1 μm or more and less than 10 μm and 80 to 300 parts by mass of water, the dispersion containing particles having a particle size of 20 to 80 μm as measured by a particle counter at a concentration of 5 to 100 particles / ml, to form a coating layer made of the dispersion on the surface of the metal foil, and heating the metal foil having the coating layer to form a resin layer containing a molten sintered body of the tetrafluoroethylene-based polymer on the surface of the metal foil. [7] The production method according to [6], wherein the content of the tetrafluoroethylene-based polymer particles is 30% by mass or more. [8] The method according to [6] or [7], wherein the dispersion further contains 5 to 20 parts by mass of a water-soluble solvent having a surface tension of 20 to 30 mN / m.
[0006] [9] A long resin-layered metal foil having, in this order, a metal foil and a resin layer containing a molten sintered body of particles of a tetrafluoroethylene-based polymer, wherein the ratio of the thickness of the resin layer to the total thickness of the long resin-layered metal foil is less than 50%, and when the resin layer is divided at intervals of 200 mm in the short direction (TD direction), the most extreme divided parts are the TD direction ends and the central divided parts are the TD direction central parts, the ten-point average roughness Rz of the TD direction ends of the surface of the resin layer on the side not in contact with the metal foil is jis Value (end Rz jis value), and Rz of the center in the TD direction jis Value (center Rz jis value) are less than 1.5 μm, and the central Rz jis Edge Rz for value jis A resin-coated metal foil with a width of 1000 mm or more, in which the value ratio is within the range of 1±0.5.
[10] The tetrafluoroethylene-based polymer contains, in this order, more than 97.5 mol % and less than 99.5 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), and the carbonyl group-containing group is 1×10 carbon atoms constituting the polymer main chain. 6 or a polymer having 100 or more per unit, or a polymer containing 90 mol% or more but less than 97.5 mol% and more than 2.5 mol% but not more than 10 mol% of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), respectively, in that order, and the number of carbonyl group-containing groups is 1×10 6 The long resin-layered metal foil according to [9], wherein the polymer has less than 100 particles per particle.
[11] The long resin-layered metal foil according to [9] or
[10] , wherein the ratio of the thickness of the resin layer to the entire thickness of the resin-layered metal foil is 35 to 48%.
[12] The long resin layer-attached metal foil according to any one of [9] to
[11] , wherein the thickness of the metal foil is 5 μm or more and 50 μm or less.
[13] A method for producing a long resin-layered metal foil according to any one of [9] to
[12] , comprising coating a metal foil with a dispersion containing 100 parts by mass of tetrafluoroethylene-based polymer particles having an average particle size of 1 μm or more and less than 10 μm and 80 to 300 parts by mass of water, the dispersion containing particles having a particle size of 20 to 80 μm as measured by a particle counter at a concentration of 5 to 100 particles / ml, to form a coating layer made of the dispersion on the surface of the metal foil, and heating the metal foil having the coating layer to form a resin layer containing a molten sintered body of the tetrafluoroethylene-based polymer on the surface of the metal foil.
[14] The production method according to
[13] , wherein the content of the tetrafluoroethylene-based polymer particles is 30% by mass or more.
[15] The method according to
[14] , wherein the dispersion further contains 5 to 20 parts by mass of a water-soluble solvent having a surface tension of 20 to 30 mN / m. Effect of the Invention
[0007] According to the present invention, there can be provided a long resin-layered metal foil, which includes a resin layer containing a tetrafluoroethylene polymer, has excellent adhesion to a conductive layer, has low transmission loss in the high frequency range, and is furthermore suppressed in occurrence of wrinkles and warping, and a method for producing the same. The long resin-layered metal foil of the present invention can be effectively used, for example, as a printed wiring board material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The following terms have the following meanings. The term "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit." "Melting temperature" is the temperature corresponding to the maximum of the melting peak of a polymer as measured by differential scanning calorimetry (DSC). The "glass transition temperature (Tg)" is a value measured by analyzing a polymer using the dynamic mechanical analysis (DMA) method. "Average particle size (D50)" is the volume-based cumulative 50% diameter of particles determined by laser diffraction / scattering. In other words, particle size distribution is measured by laser diffraction / scattering, and a cumulative curve is calculated with the total volume of the particle group as 100%, and the particle size is the point on the cumulative curve where the cumulative volume is 50%. The D50 of particles is determined by dispersing the particles in water and analyzing them by the laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). "Average particle size (D90)" is the volume-based cumulative 90% diameter of the particles, calculated in the same manner as for D50. The specific surface area of a particle is a value calculated by measuring the particle by a gas adsorption (constant volume method) BET multipoint method, and is determined using a NOVA4200e (manufactured by Quantachrome Instruments). The "viscosity" is determined by measuring the composition using a Brookfield viscometer at 25° C. and 30 rpm. The measurement is repeated three times, and the average value of the three measured values is calculated. The "thixotropy ratio" is a value calculated by dividing the viscosity η1 of the composition measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement is repeated three times, and the average value of the three measured values is used. The "surface tension" of a solvent or solution is a value measured by the Wilhelmy method at 25°C using a surface tensiometer.
[0009] The long resin-layered metal foil of the present invention (hereinafter also referred to as "the present long resin-layered metal foil") has a metal foil and a resin layer (hereinafter also referred to as "F layer") containing a molten sintered body of particles (hereinafter also referred to as "F particles") of a tetrafluoroethylene-based polymer (hereinafter also referred to as "F polymer") in this order, the ratio of the thickness of the F layer to the entire thickness of the present resin-layered metal foil is less than 50%, and when the F layer is divided at intervals of 200 mm in the short direction (TD direction), When the divided parts of the ends are defined as the TD end parts and the divided parts of the central part are defined as the TD central part, the root mean square height Rq value (end Rq value) of the TD end part and the root mean square height Rq value (central Rq value) of the TD central part on the surface not in contact with the metal foil of F layer are each less than 0.5 μm, and the ratio of the end Rq value to the central Rq value is in the range of 1±0.5. The long resin-layered metal foil also has a ten-point average roughness Rz of the end in the TD direction on the surface of the side not in contact with the metal foil of the F layer. jis Value (end Rz jis value), and the ten-point average roughness Rz jis Value (center Rz jis value) are less than 1.5 μm, and the central Rz jis Edge Rz for value jis It is preferred that the ratio of values is in the range of 1±0.5.
[0010] This long-length resin-coated metal foil has physical properties based on the F polymer, such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant, and low dielectric tangent), as well as excellent adhesion to the metal foil conductive layer, and is equipped with a resin layer that has low transmission loss in the high frequency range. Furthermore, when handled as a long body such as a roll, the occurrence of wrinkles and warping is suppressed. In the present long resin-layered metal foil, the reason why the resin layer has excellent adhesion to the metal foil and the occurrence of wrinkles and warping is suppressed is not entirely clear, but is thought to be as follows.
[0011] When the resin layer containing an F polymer, which accounts for the entire thickness of the resin-layered metal foil, contains a molten sintered body of F polymer particles, the voids present between the sintered particles can act to buffer the internal stress caused by the high linear expansion of the F polymer, but can also cause wrinkles and warping when external stress is applied, such as during winding or stretching. In this resin-layered metal foil, when the F layer is divided in the short direction (TD direction) at intervals of 200 mm, the most extreme divided parts are the TD direction ends, and the central divided part is the TD direction central part, the relationship between the root mean square height Rq value of the TD direction ends (end Rq value) and the root mean square height Rq value of the TD direction central part (central Rq value) of the surface of the F layer not in contact with the metal foil, or further the ten-point average roughness Rz jis Value (end Rz jis value), and the ten-point average roughness Rz jis Value (center Rz jis The relationship between the two values satisfies a specified range. In other words, the surface roughness of the F layer is expressed as the root mean square height Rq value or the ten-point average roughness Rz jis From the viewpoint of the values, these values are converged to a predetermined range in the TD direction of the resin-coated metal foil. This is considered to have the effect of absorbing or cushioning the internal stress in the F layer, as well as mitigating the external stress when handling it as a long body such as a roll, thereby suppressing the occurrence of wrinkles and warping. It is also assumed that such control of the surface properties of the F layer has improved the adhesion with the metal foil, which is the conductive layer.
[0012] Examples of the metal foil constituting the present resin-layered metal foil include metal foils of copper, nickel, aluminum, titanium, alloys thereof, etc. Among these, copper foil is preferred. The thickness of the metal foil is preferably 1 μm or more, more preferably 5 μm or more, from the viewpoint of ensuring electrical conductivity, and is preferably 50 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less, taking into consideration the thickness of the entire printed wiring board.
[0013] The ratio of the thickness of the F layer to the entire thickness of the present resin-layered metal foil is less than 50%, and more preferably 48% or less. On the other hand, from the viewpoint that the present resin-layered metal foil can fully exhibit the properties based on the F polymer, the ratio of the thickness of the F layer to the entire thickness of the present resin-layered metal foil is preferably 35% or more. That is, the ratio of the thickness of the F layer to the entire thickness of the present resin-layered metal foil is preferably 35 to 48%, and taking such a ratio into consideration, the thickness of the F layer constituting the present resin-layered metal foil is preferably 1 μm or more, more preferably 5 μm or more. The thickness of the F layer is preferably 50 μm or less, more preferably 20 μm or less, even more preferably 15 μm or less, and particularly preferably 10 μm or less.
[0014] The dielectric constant of the F layer is preferably 2.4 or less, more preferably 2.0 or less. Also, the dielectric constant is preferably greater than 1.0. The dielectric tangent of the F layer is preferably 0.0022 or less, more preferably 0.0020 or less. Also, the dielectric tangent is preferably greater than 0.0001. The thermal conductivity of the F layer is preferably 1 W / m·K or more, more preferably 3 W / m·K or more. The upper limit of the thermal conductivity of the F layer is 100 W / m·K. The thermal conductivity of the F layer means the thermal conductivity in the in-plane direction of the F layer.
[0015] The linear expansion coefficient of the F layer is preferably 100 ppm / ° C. or less, more preferably 80 ppm / ° C. or less. The lower limit of the linear expansion coefficient of the F layer is 10 ppm / ° C. The linear expansion coefficient means a value obtained by measuring the linear expansion coefficient of a test piece in the range of 25° C. or more and 260° C. or less according to the measurement method specified in JIS C 6471:1995. The peel strength between the F layer and the metal foil is preferably 10 N / cm or more, more preferably 15 N / cm or more, and is preferably 100 N / cm or less.
[0016] In this resin-layered metal foil, when the F layer is divided in the short direction (TD direction) at 200 mm intervals, with the endmost divided parts being the TD direction end parts and the central divided part being the TD direction central part, the root-mean-square height Rq value (end Rq value) of the TD direction end part and the root-mean-square height Rq value (central Rq value) of the TD direction central part on the surface of the F layer not in contact with the metal foil are each less than 0.5 μm, and the ratio of the end Rq value to the central Rq value is in the range of 1±0.5. Both the end Rq value and the center Rq value are preferably 0.4 μm or less, and more preferably 0.3 μm or less. On the other hand, both the end Rq value and the center Rq value are preferably 0.01 μm or more. Also, the ratio of the end Rq value to the center Rq value is preferably in the range of 1±0.40, and more preferably in the range of 1±0.25. The long resin-layered metal foil also has a ten-point average roughness Rz of the end in the TD direction on the surface of the side not in contact with the metal foil of the F layer. jis Value (end Rz jis value), and the ten-point average roughness Rz jis Value (center Rz jis value) are less than 1.5 μm, and the central Rz jis Edge Rz for value jis It is preferred that the ratio of values is in the range of 1±0.5. End Rz jis Value and central Rz jis In any case, the value is more preferably 1.2 μm or less, and further preferably 0.8 μm or less. jis Value and central Rz jis It is preferable that each value is 0.01 μm or more. Also, the central Rz jis Edge Rz for value jis More preferably, the ratio of values is in the range of 1±0.40, and even more preferably in the range of 1±0.25. The root mean square height Rq value is within the above range, preferably the Rq value and the ten-point average roughness Rz jis When both values are within the above ranges, the above-mentioned effects are more pronounced, and the occurrence of wrinkles and warping can be suppressed when the film is handled as a long body such as a roll, etc. Also, the adhesive strength between the F layer and the base layer can be maintained. In this specification, the root mean square height Rq value and the ten-point average roughness Rz jis The value means a value measured, for example, by a laser microscope in accordance with JIS B 0601-2001 (line roughness).
[0017] The F polymer in the present invention is a polymer containing units based on tetrafluoroethylene (hereinafter also referred to as "TFE") (hereinafter also referred to as "TFE units"). The F polymer is preferably heat-fusible. Here, a heat-fusible polymer means a polymer that has a temperature at which the melt flow rate is 1 to 1000 g / 10 min under a load of 49 N. The melting temperature of the F polymer is preferably 200° C. or higher, more preferably 260° C. or higher. The melting temperature of the F polymer is preferably 325° C. or lower, more preferably 320° C. or lower. The melting temperature of the F polymer is preferably 200 to 320° C. In this case, the F layer tends to have excellent heat resistance.
[0018] The glass transition point of the F polymer is preferably 50° C. or higher, more preferably 75° C. or higher. The glass transition point of the F polymer is preferably 150° C. or lower, more preferably 125° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a droplet of a mixture for wetting tension testing (manufactured by Wako Pure Chemical Industries, Ltd.) specified in JIS K 6768 on a flat plate made of the F polymer.
[0019] F polymer is preferably a polymer containing TFE unit and ethylene-based unit (ETFE), a polymer containing TFE unit and propylene-based unit, a polymer containing TFE unit and perfluoro(alkyl vinyl ether) (PAVE)-based unit (PAVE unit) (PFA), a polymer containing TFE unit and hexafluoropropylene-based unit (FEP), more preferably PFA and FEP, and even more preferably PFA. These polymers may further contain units based on other comonomers. PAVE is preferably CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE"), and more preferably PPVE.
[0020] The F polymer preferably has an oxygen-containing polar group, more preferably has a hydroxyl- or carbonyl-containing group, and even more preferably has a carbonyl-containing group. In this case, the F layer tends to have excellent physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric tangent). The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.), a formyl group, a halogenoformyl group, a urethane group (-NHC(O)O-), a carbamoyl group (-C(O)-NH2), a ureido group (-NH-C(O)-NH2), an oxamoyl group (-NH-C(O)-C(O)-NH2) or a carbonate group (-OC(O)O-), and more preferably an acid anhydride residue. When the F polymer has an oxygen-containing polar group, the number of oxygen-containing polar groups in the F polymer is 1×10 6The number of oxygen-containing polar groups per unit is preferably 10 to 5000, more preferably 100 to 3000. The number of oxygen-containing polar groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133.
[0021] The oxygen-containing polar group may be contained in a unit based on a monomer in the F polymer, or may be contained in a terminal group of the main chain of the F polymer, the former being preferred. The latter embodiment includes an F polymer having an oxygen-containing polar group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment.
[0022] The F polymer contains TFE units and PAVE units in the order of more than 97.5 mol% and less than 99.5 mol%, and 0.5 mol% or more and less than 2.5 mol%, and has a carbonyl group-containing group in an amount of 1×10 6 or a polymer (1) containing TFE units and PAVE units in the order of 90 mol % or more and less than 97.5 mol %, more than 2.5 mol % and 10 mol % or less, and the number of carbonyl group-containing groups is 1×10 6 Polymers (2) having less than 100 per unit area are preferred. If such an F polymer is used, spherulites having a relatively small radius are easily formed, so that the surface roughness of the F layer is easily improved, and the root mean square height Rq value and the ten-point average roughness Rz value are within the above-mentioned predetermined range. jis Easy to control the value.
[0023] The polymer (1) is more preferably a polymer containing TFE units, PAVE units, and units based on a monomer having a carbonyl group-containing group, and containing these units in the order of more than 97.5 mol% and less than 99.5 mol%, 0.5 mol% or more and less than 2.2 mol%, and 0.01 to 0.3 mol% relative to the total units. Specific examples of such F polymers include the polymers described in WO 2018 / 16644. The monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"), and more preferably NAH.
[0024] The polymer (2) is more preferably composed of only TFE units and PAVE units, and contains more than 2.5 mol % and not more than 5.0 mol % of PAVE units based on all units. The number of carbonyl-containing groups in polymer (2) is 1×10 6 More preferably, the number per carbonyl group is less than 50. The lower limit of the number of the carbonyl group-containing groups is 1. The polymer (2) may be produced by using a polymerization initiator or a chain transfer agent that does not generate a carbonyl group-containing group as a terminal group of the polymer chain, or by fluorinating an F polymer having a carbonyl group-containing group (such as an F polymer having an oxygen-containing polar group derived from a polymerization initiator at the terminal group of the polymer main chain). Examples of the fluorination method include a method using fluorine gas (see JP 2019-194314 A, etc.).
[0025] The present resin-layered metal foil can be suitably produced, for example, by coating a metal foil with a dispersion (hereinafter also referred to as "the present dispersion") containing 100 parts by mass of F polymer particles having an average particle size of 1 μm or more and less than 10 μm and 80 to 300 parts by mass of water, and having a particle concentration of 5 to 100 particles / ml having a particle size of 20 to 80 μm as measured with a particle counter, to form a coating layer made of the present dispersion on the surface of the metal foil, and heating the metal foil having the coating layer to form an F layer on the surface of the metal foil. That is, the present invention also relates to a method for producing a long resin-layered metal foil (hereinafter also referred to as "the method"), which comprises applying the present dispersion to a metal foil to form a coating layer made of the present dispersion on the surface of the metal foil, and heating the metal foil having the coating layer to form a resin layer containing a molten sintered body of the F polymer on the surface of the metal foil.
[0026] In this method, the F particles contained in the dispersion are particles that include an F polymer, and preferably consist of an F polymer. The D50 of the F particles is 1 μm or more and less than 10 μm. The F particles may be solid particles or non-hollow particles. The F particles may be secondary particles formed from nanometer-order fine particles. The D50 of the F particles is preferably 1.0 μm or more, more preferably 1.5 μm or more. The D50 of the F particles is preferably 6 μm or less, more preferably 5 μm or less. Furthermore, D90 of the F particles is preferably 8 μm or less, and more preferably 6 μm or less. When the D50 and D90 of the F particles are within the above ranges, the dispersion liquid is likely to have excellent dispersion stability and handleability, and the dispersion liquid is likely to have a particle concentration of 5 to 100 particles / ml having a particle diameter of 20 to 80 μm as measured with a particle counter. One type of F particle may be used, or two or more types of F particles may be used.
[0027] The specific surface area of F particles is 1 to 25 m 2 / g, and 6 to 15m 2 When the specific surface area of the F particles is within the above range, it is considered that the surfaces of the F particles are easily wetted and aggregates of the F particles are easily disintegrated, making it easier to obtain a dispersion liquid in which the concentration of particles having particle diameters of 20 to 80 μm measured with a particle counter is 5 to 100 particles / ml. In addition, the F layer formed on the coating layer made of the present dispersion, preferably through a stepwise heating process, has the above-mentioned root mean square height Rq value or ten-point average roughness Rz jis It is easier for the material to satisfy the specified range of values, and in addition to the physical properties based on the F polymer, such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric tangent), it is easier for the material to have excellent adhesion to the base layer, and the occurrence of wrinkles and warping is easier to suppress when it is handled as a long body such as a roll.
[0028] This dispersion contains 100 parts by mass of F particles and 80 to 300 parts by mass of water, and has a particle concentration of 5 to 100 particles / ml having a particle diameter of 20 to 80 μm as measured with a particle counter. The content of F particles in the present dispersion is preferably 25% by mass or more, more preferably 30% by mass or more, and is preferably 55% by mass or less, more preferably 50% by mass or less. The water content in the present dispersion is preferably 25% by mass or more, and more preferably 40% by mass or more. The water content is preferably less than 70% by mass, and more preferably 65% by mass or less. The water content in the present dispersion is preferably 60 to 180% by mass relative to the F particle content. In the present dispersion, the particle concentration of particles having a particle diameter of 20 to 80 μm as measured by a particle counter is preferably 10 particles / ml or more. The particle concentration is preferably 80 particles / ml or less, more preferably 60 particles / ml or less. When the particle concentration is within the above range, the above-mentioned mechanism of action is more easily manifested, and the above-mentioned root mean square height Rq value or ten-point average roughness Rz of the F layer obtained by the present method is more easily manifested. jis It becomes easier to control the value within a specific range.
[0029] The dispersion may further contain 5 to 20 parts by mass of a water-soluble solvent having a surface tension of 20 to 30 mN / m. The water-soluble solvent having a surface tension of 20 to 30 mN / m is a compound that is liquid at 25°C under atmospheric pressure, preferably a compound having a boiling point of 160°C or less, more preferably a compound having a boiling point of 120°C or less. Such a water-soluble solvent is preferably azeotropic with water. In this specification, the water-soluble solvent means a solvent having a solubility in water of 100 g / L or more. The water-soluble solvent is preferably a monool having 1 to 6 carbon atoms, more preferably methanol (23 mN / m), ethanol (23 mN / m), 1-propanol (24 mN / m), 2-propanol (22 mN / m), 1-butanol (25 mN / m), 2-butanol (24 mN / m), isobutanol (23 mN / m), 1-methoxy-2-propanol (26 mN / m), 2-propoxy-ethanol (27 mN / m), 1-propoxy-2-propanol (25 mN / m), 2-ethoxyethanol (26 mN / m), and even more preferably ethanol. The numerical values in parentheses are the surface tensions of the monools. When the present dispersion further contains a water-soluble solvent, the amount is preferably 0.1 to 5 mass % or less based on the total amount of the present dispersion. The content of the water-soluble solvent in the present dispersion is preferably 1 to 10 mass % based on the content of the F particles. In the present dispersion, the water-soluble solvent is considered to play a role in adjusting the concentration of particles with a particle size of 20 to 80 μm, and also to play a role as an antifoaming agent such as a foam suppressing action or a foam breaking action.
[0030] The dispersion may further contain a nonionic surfactant, such as a glycol surfactant, an acetylene surfactant, a silicone surfactant, or a fluorine surfactant. Among these, nonionic surfactants having a hydroxyl group in the hydrophilic site are preferred, and organopolysiloxanes having a hydroxyl group or a polyoxyalkylene group are more preferred. When the present dispersion contains the above-mentioned nonionic surfactant, the above-mentioned mechanism of action is more easily manifested, and the dispersion stability and handleability of the F particles are more likely to be excellent. Furthermore, the rheological properties of the dispersion are improved, and handling properties such as film-forming properties tend to improve. The organopolysiloxane is more preferably a polyoxyalkylene-modified dimethylsiloxane having a polyoxyalkylene structure as the hydrophilic portion and a polydimethylsiloxane structure as the hydrophobic portion. Polyoxyalkylene-modified dimethylsiloxane has a polydimethylsiloxane unit (-(CH3)2SiO2 / 2 -), may have polydimethylsiloxane units in the side chain, or may have polydimethylsiloxane units in both the main chain and the side chain.
[0031] Specific examples of nonionic surfactants include the "Ftergent" series (manufactured by Neos), the "Surflon" series (manufactured by AGC Seimi Chemical Co., Ltd.), the "Megafac" series (manufactured by DIC Corporation), the "Unidyne" series (manufactured by Daikin Industries, Ltd.), "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (manufactured by BYK Japan), "KF-6011", "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.), and the "Tergitol" series (manufactured by The Dow Chemical Company, "Tergitol TMN-100X", etc.). The nonionic surfactant may be used alone or in combination of two or more kinds. When the present dispersion further contains a nonionic surfactant, the amount thereof is preferably within a range of 1 to 15 parts by mass relative to 100 parts by mass of the present dispersion.
[0032] The dispersion may further contain a water-soluble polymer, such as at least one selected from the group consisting of vinyl alcohol polymers, acrylic polymers, polyvinylpyrrolidone, polypyrrole, polythiophene, polyethyleneimine, and cellulose ether. In this specification, the term "water-soluble polymer" refers to a polymer having a solubility in water of 20 g / L or more. When the present dispersion contains the above-mentioned water-soluble polymer, the above-mentioned mechanism of action is more easily exhibited, and the concentration of particles having a particle size of 20 to 80 μm in the present dispersion can be easily adjusted to a predetermined range, and the rheological properties of the present dispersion are improved, and the handling properties such as film-forming properties are easily improved.
[0033] Examples of vinyl alcohol-based polymers include polyvinyl alcohol, polyvinyl acetate, partially acetylated or partially acetalized polyvinyl alcohol, and copolymers of vinyl alcohol, vinyl butyral, and vinyl acetate. Specific examples of vinyl alcohol-based polymers include the "S-LEC (registered trademark) B" series, the "S-LEC (registered trademark) K (KS)" series, and the "S-LEC (registered trademark) SV" series (all manufactured by Sekisui Chemical Co., Ltd.), and the "Mobital (registered trademark)" series (manufactured by Kuraray Co., Ltd.).
[0034] Specific examples of cellulose ethers include the "Sunrose (registered trademark)" series (manufactured by Nippon Paper Industries Co., Ltd.), the "Metolose (registered trademark)" series (manufactured by Shin-Etsu Chemical Co., Ltd.), and "HEC CF Grade" (manufactured by Sumitomo Seika Chemicals Co., Ltd.). The water-soluble polymer may be used alone or in combination with two or more kinds. When the present dispersion further contains a water-soluble polymer, the amount thereof is preferably within a range of 1 to 15 parts by mass relative to 100 parts by mass of the present dispersion.
[0035] In addition to water and the above-mentioned water-soluble solvent, the present dispersion may contain other dispersion media within the range that does not impair the effects of the present invention. Such other dispersion media are preferably miscible with the above-mentioned water-soluble solvent and water. Examples of other dispersion media include amides such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone; and ketones such as acetone and methyl ethyl ketone.
[0036] Here, the concentration of particles having a particle diameter of 20 to 80 μm as measured by a particle counter in this dispersion can be controlled to 5 to 100 particles / ml by, for example, using F particles having a specific specific surface area using a specific F polymer and dispersing them by controlling the blend ratio with water, and further including one or more of the above-mentioned water-soluble solvents, nonionic surfactants, and water-soluble polymers.
[0037] The present dispersion may further contain inorganic particles, in which case the F layer formed from the present dispersion is likely to have excellent electrical properties and low linear expansion. Examples of inorganic particles include silicon compounds such as quartz powder, silica, wollastonite, talc, silicon nitride, silicon carbide, and mica; nitrogen compounds such as boron nitride and aluminum nitride; metal oxides such as aluminum oxide, zinc oxide, titanium oxide, cerium oxide, beryllium oxide, magnesium oxide, nickel oxide, vanadium oxide, copper oxide, iron oxide, and silver oxide; carbon fibers; carbon allotropes such as graphite, graphene, and carbon nanotubes; and metals such as silver and copper. One type of inorganic particle may be used, or two or more types may be used in combination.
[0038] The present dispersion may further contain another resin different from the F polymer. Such another resin may be contained in the present dispersion as non-hollow particles, or may be dissolved or dispersed in a liquid dispersion medium (hereinafter also referred to as "liquid dispersion medium") such as water, a water-soluble solvent, or another dispersion medium that constitutes the present dispersion. As the other resin, aromatic polymers are preferable, for example, aromatic imide polymers can be mentioned.Specific examples of aromatic imide polymers include "UPIA-AT" series (UBE), "NEOPLIM (registered trademark)" series (Mitsubishi Gas Chemical Company, Inc.), "SPIXELIA (registered trademark)" series (Somar), "Q-PILON (registered trademark)" series (PI Technical Research Institute), "WINGO" series (Wingo Technology Co., Ltd.), "TOMAID (registered trademark)" series (T&K TOKA), "KPI-MX" series (Kawamura Sangyo Co., Ltd.), "HPC-1000" and "HPC-2100D" (both manufactured by Showa Denko Materials Co., Ltd.). When the present dispersion further contains another resin, the content of the other resin relative to the F particles is preferably 1 to 25% by weight.
[0039] The present dispersion may further contain additives such as a thixotropic agent, a viscosity modifier, an antifoaming agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, and a flame retardant.
[0040] The present dispersion is obtained by mixing 100 parts by mass of F particles, 80 to 300 parts by mass of water, and, if necessary, the water-soluble solvent, nonionic surfactant, other dispersion medium, inorganic particles, other resins, additives, etc. The present dispersion may be obtained by mixing F particles and water all at once, or by dividing and mixing them several times. In addition, there is no particular limitation on the order of mixing when the water-soluble solvent, nonionic surfactant, other dispersion medium, inorganic particles, other resins, additives, etc. are further mixed as necessary, and they may be mixed with the F particles in advance, may be added to water in advance and then mixed with the F particles, or may be mixed when the F particles and water are mixed.
[0041] Examples of mixing devices for obtaining the present dispersion include stirring devices equipped with blades, such as a Henschel mixer, a pressure kneader, a Banbury mixer, and a planetary mixer; grinding devices equipped with media, such as a ball mill, an attritor, a basket mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, a spike mill, and an agitator mill; and dispersing devices equipped with other mechanisms, such as a microfluidizer, a nanomizer, an ultimizer, an ultrasonic homogenizer, a dissolver, a disperser, a high-speed impeller, a thin film swirling high-speed mixer, a planetary stirrer, and a V-type mixer.
[0042] The viscosity of the present dispersion is preferably 10 mPa·s or more, more preferably 100 mPa·s or more. The viscosity of the present dispersion is preferably 10,000 mPa·s or less, more preferably 3,000 mPa·s or less. In this case, the present dispersion has excellent coatability and is easy to form an F layer of any thickness. In addition, the present dispersion having a viscosity in this range is easy to highly express the physical properties of the F polymer in the F layer formed therefrom. The thixotropy ratio of the present dispersion is preferably 1.0 to 3.0, in which case the present dispersion has excellent coatability and homogeneity and is likely to produce a denser F layer. These liquid properties are likely to be improved when the present dispersion further contains the above-mentioned water-soluble polymer.
[0043] From the viewpoint of improving long-term storage stability, the pH of the present dispersion is more preferably 8 to 10. The pH of the present dispersion can be adjusted with a pH adjuster (amine, ammonia, citric acid, etc.) or a pH buffer (tris(hydroxymethyl)aminomethane, ethylenediaminetetraacetic acid, ammonium hydrogen carbonate, ammonium carbonate, ammonium acetate, etc.).
[0044] In this method, the present dispersion is applied to a long metal foil to form a coating layer of the present dispersion on the surface of the metal foil. Examples of the method for applying the present dispersion include a coating method, a droplet ejection method, and a dipping method, and the present dispersion is preferably applied to a roll coating method, a knife coating method, a bar coating method, a die coating method, or a spray method. The ten-point average roughness of the surface of the metal foil is preferably 0.01 to 0.05 μm. The surface of the metal foil may be surface-treated with a silane coupling agent or may be plasma-treated. As such a silane coupling agent, a silane coupling agent having a functional group such as 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, or 3-isocyanatepropyltriethoxysilane is preferable. This method can be applied to a roll-to-roll process, and the resin-coated metal foil can be manufactured as a long product such as a roll. In addition, the resin-coated metal foil obtained as a long product such as a roll is less likely to wrinkle or warp, which is preferable from the viewpoint of improving productivity.
[0045] Next, the metal foil having the coating layer is heated. It is preferable to perform such heating in stages. Specifically, in the first heating, the coating layer is heated near the glass transition temperature while maintaining the diffusion state of the F particles in the coating layer, giving priority to minimizing changes in the state of the F particles themselves. On the other hand, in the second heating, the diffusion and removal of the liquid dispersion medium such as water or a water-soluble solvent from the coating layer is given priority to form a layer containing F particles, which is a dry coating with little distortion overall. Then, it is preferable to bake the dry coating to form a resin layer containing an F polymer. By this stepwise drying, even if a dispersion liquid containing F particles, which generally have low affinity with other materials, is used, the F particle aggregation is highly eliminated, and the diffusion of the F particles and the diffusion of the liquid dispersion medium are balanced, and the root mean square height Rq value or the ten-point average roughness Rz value in the F layer is reduced. jis It is considered that it is easy to form an F layer that has high adhesion and low transmission loss and is suppressed from wrinkling or warping when handled as a long body such as a roll. jis It is believed that an F layer having such a value tends to adhere tightly and firmly due to the anchor effect with the metal foil such as copper foil and the increased contact area, resulting in a smaller dielectric loss. This tendency becomes more pronounced when the dispersion liquid further contains one or more of a water-soluble solvent, a nonionic surfactant, or a water-soluble polymer having a specific surface tension, because the surface of the F particles becomes more easily wetted, and the F particle aggregates are more easily broken down and uniformly dispersed.
[0046] As the stepwise heating, it is preferable to first heat the metal foil in a temperature range of 25°C or higher, lower than the boiling point of the water constituting the dispersion and lower than [the glass transition temperature of the F polymer + 10°C], and then to heat the metal foil in a temperature range higher than the above temperature range and lower than the melting temperature of the F polymer, thereby obtaining a metal foil having a layer containing F particles on its surface. The lower limit of the initial heating temperature is preferably 40° C. or higher. The upper limit of the initial heating is preferably below the glass transition temperature of the F polymer. The second heating is preferably carried out in a temperature range that is 50° C. or more higher than the temperature range of the first heating and is equal to or lower than the melting temperature of the F polymer minus 100° C. Specifically, it is preferable that the temperature range of the first heating is 45 to 95°C, and the temperature range of the second heating is 100 to 150°C.
[0047] The above-mentioned first heating and second heating are both preferably performed for 1 to 30 minutes. In the first heating and second heating, the liquid dispersion medium does not need to be completely removed, and it is sufficient to remove it to the extent that the layer formed by the packing of the F particles can maintain a self-supporting film. In addition, in the first heating and second heating, air may be blown to promote removal of the liquid dispersion medium by air drying.
[0048] It is preferable to further heat the metal foil having a layer containing F particles on its surface obtained by the second heating (hereinafter also referred to as "third heating") in a temperature range equal to or higher than the melting temperature of the F polymer to form an F layer on the surface of the metal foil, thereby obtaining the present metal foil with a resin layer. Specifically, the temperature range of the third heating is preferably 340 to 400° C. Furthermore, the heating time of the third heating is preferably 0.1 to 30 minutes.
[0049] The heating device for each of the first heating, the second heating, and the third heating may be an oven or a ventilation drying furnace. The heat source in the device may be a contact type heat source (hot air, hot plate, etc.) or a non-contact type heat source (infrared rays, etc.). In this method, each heating step may be performed under normal pressure (atmospheric pressure) or reduced pressure, and the atmosphere in each heating step may be either air or inert gas (helium gas, neon gas, argon gas, nitrogen gas, etc.).
[0050] The F layer is formed through a process of coating the present dispersion on a metal foil and heating, preferably through each of the heating processes of the first heating, the second heating, and the third heating described above. These processes may be performed once each, or may be repeated two or more times. For example, the present dispersion may be coated on the surface of a metal foil to obtain a coating layer, and an F layer may be formed by the first heating, the second heating, and the third heating, and the present dispersion may be further coated on the surface of the F layer to form a coating layer, and the second F layer may be formed by each of the heating processes described above. Alternatively, the present dispersion may be coated on the surface of a metal foil to obtain a coating layer, and at the stage where the liquid dispersion medium is removed by the first heating and the second heating, the present dispersion may be further coated on the surface, and the F layer may be formed by each of the heating processes described above. The first heating may be carried out stepwise at a plurality of temperatures within the temperature range of the first heating, and the second heating may be carried out stepwise at a plurality of temperatures within the temperature range of the second heating.
[0051] After heating for baking the F polymer, the temperature is lowered to at least the melting temperature of the F polymer to obtain the present resin-layered metal foil. There is no particular limit to the rate of temperature lowering, and the foil may be left to cool in air or may be appropriately cooled by water cooling or the like. The rate of temperature lowering may also be controlled, for example, by using a temperature control function associated with the above-mentioned oven or ventilated drying furnace as a heating device.
[0052] The resin-layered metal foil may be further laminated with other layers, such as heat-resistant resin films of liquid crystal polymers such as polyimide, polyamide, polyetheramide, polyphenylene sulfide, polyaryl ether ketone, polyamideimide, liquid crystal polyester, and tetrafluoroethylene-based polymers other than F polymers, such as polytetrafluoroethylene; prepreg substrates (precursors of fiber-reinforced resin substrates), ceramic substrates such as silicon carbide, aluminum nitride, and silicon nitride; and glass substrates.
[0053] The present invention also provides a long resin-layered metal foil having, in this order, a metal foil and a resin layer (F layer) containing a molten sintered body of F polymer particles, wherein the ratio of the thickness of the F layer to the overall thickness of the long resin-layered metal foil is less than 50%, and when the F layer is divided in the short direction (TD direction) at intervals of 200 mm, the most extreme divided parts are the TD direction ends and the central divided part is the TD direction central part, the ten-point average roughness Rz of the TD direction ends of the surface of the F layer on the side not in contact with the metal foil is 1 / 1000,000,000,000, and the F layer is 1 / 1 ... jis Value (end Rz jis value), and Rz of the center in the TD direction jis Value (center Rz jis value) are less than 1.5 μm, and the central Rz jis Edge Rz for value jis The ratio of these values is in the range of 1±0.5, and the length of the resin-layered metal foil is 1000 mm or more in width (hereinafter, also referred to as "long resin-layered metal foil α"). In the long resin-coated metal foil α, the details of the metal foil and the F layer are the same as those of the metal foil and the F layer in the resin-coated metal foil described above. jis Value (end Rz jis value) and Rz at the center in the TD direction jis Value (center Rz jis The value) and its preferred range are also as described above in the explanation of the present resin-layered metal foil. In addition, the long resin-layered metal foil α can be preferably produced by the above-mentioned method, in which the present dispersion is applied to a metal foil to first form a coating layer made of the present dispersion on the surface of the metal foil, and then the metal foil having the coating layer is heated to form a resin layer containing a molten-sintered body of F particles on the surface of the metal foil.
[0054] The resin-layered metal foil is useful for antenna parts, printed circuit boards, aircraft parts, automobile parts, heat dissipation parts, and the like. Specifically, wire coating materials (aircraft wires, rectangular wires, FFC (Flexible flat cables), etc.), enameled wire coating materials used in motors for electric vehicles, etc., power generation coating materials, electrical insulating tape, insulating tape for oil drilling, oil transport hoses, hydrogen tanks, materials for printed circuit boards, carrier films for fuel cells, tape base films for semiconductor manufacturing processes (dicing tape, pick-up tape, etc.), release films for semiconductor molding, liquid crystal antennas, reflectors, transmission paths, base films for COF (Chip on film), electrostatic chucks for semiconductor manufacturing processes, electrostatic chucks for display manufacturing processes, copy rolls, heat dissipation substrates for mounting power devices, heat dissipation materials for wireless communication devices, transistors, thyristors, rectifiers, transformers, power MOS They are useful as FETs, CPUs, heat dissipation fins, metal heat sinks, blades for wind turbines, wind power generation equipment, and aircraft, housings for personal computers and displays, electronic device materials, interior and exterior parts of automobiles, sealing materials for processing machines and vacuum ovens that perform heat treatment under low oxygen conditions, plasma processing equipment, heat dissipation parts in processing units for sputtering and various dry etching equipment, and electromagnetic wave shielding. In particular, the resin-layered metal foil is useful as a material for electronic substrates such as flexible printed wiring boards and rigid printed wiring boards.
[0055] Although the present resin-layered metal foil, the present method, and the long resin-layered metal foil α have been described above, the present invention is not limited to the configurations of the above-mentioned embodiments. For example, the resin-layered metal foil may have any other configuration in addition to the configurations of the above-mentioned embodiments, or may be replaced with any configuration that produces a similar effect. Furthermore, the present method may have any other process in addition to the configurations of the above-mentioned embodiments, or may be replaced with any process that produces a similar effect. EXAMPLES
[0056] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Preparation of each ingredient [F Polymer] F particle 1: A polymer having a TFE unit, a NAH unit, and a PPVE unit, each of which is 97.9 mol%, 0.1 mol%, and 2.0 mol%, respectively, and a carbonyl group-containing group having a carbon atom number of 1×10 6 Particles of tetrafluoroethylene polymer (melting point: 300°C) with 1000 particles per particle (D50: 2.0 μm, specific surface area: 7 m 2 / g) [Surfactants] Surfactant 1: A nonionic silicone surfactant having a polysiloxane chain in the main chain and a polyethylene oxide group in the side chain. [Water-soluble polymer] Water-soluble polymer 1: Hydroxyethyl cellulose Water-soluble polymer 2: Polyacrylic acid
[0057] 2. Dispersion liquid production example [Production Example 1] F particles 1, surfactant 1, water-soluble polymer 1, and water were added to the pot, and zirconia balls were then added. The pot was then rolled at 150 rpm for 1 hour to obtain dispersion liquid 1 containing F particles 1 (35 parts by mass), surfactant 1 (5 parts by mass), water-soluble polymer 1 (0.1 parts by mass), and water (59.9 parts by mass). 1.44 ml of dispersion 1 was taken and diluted 250 times. The entire amount was then passed through a particle size distribution measuring device (AccuSizer (registered trademark) A7000APS manufactured by Japan Entegris Co., Ltd., using an LE400 sensor) to measure the particle concentration with particle diameters of 20 to 80 μm, which was 20 particles / ml.
[0058] [Production Example 2] Dispersion liquid 2 containing F particles 1 (35 parts by mass), surfactant 1 (5 parts by mass), water-soluble polymer 1 (1.0 part by mass) and water (59.0 parts by mass) was obtained in the same manner as in Example 1, except that the amount of water-soluble polymer 1 was changed. 1.44 ml of Dispersion Liquid 2 was taken, and the concentration of particles with particle diameters of 20 to 80 μm was measured in the same manner as in Example 1, and was found to be 100 particles / ml. [Production Example 3] Dispersion 3 containing F particles 1 (35 parts by mass), surfactant 1 (5 parts by mass), water-soluble polymer 2 (0.1 parts by mass) and water (59.9 parts by mass) was obtained in the same manner as in Example 1, except that water-soluble polymer 2 was used instead of water-soluble polymer 1. 1.44 ml of Dispersion Liquid 3 was taken, and the concentration of particles with particle sizes of 20 to 80 μm was measured in the same manner as in Example 1, and was found to be 4 particles / ml.
[0059] 3. Manufacturing example of resin-coated metal foil [Example 1] Using a roll-to-roll process, dispersion 1 was applied to one side of copper foil (electrolytic copper foil "CF-T49A-DS-HD2", thickness 18 μm, manufactured by Fukuda Metal Foil & Powder Co., Ltd.) using a small diameter gravure reverse method to form a coating layer, and the coating layer was passed through a ventilated dryer at a furnace temperature of 70°C for 5 minutes to perform the first heating, and then passed through a ventilated dryer at a furnace temperature of 150°C for 3 minutes to perform the second heating, thereby forming copper foil having a dry film containing F particles 1 on its surface. Furthermore, the copper foil having this dry film on its surface was passed through a far-infrared furnace at a furnace temperature of 350°C for 5 minutes to melt and sinter the F particles 1, forming a resin layer (thickness 15 μm) containing the molten and sintered F particles 1 on the surface of the copper foil, and a long resin-layered copper foil 1 having a width of 1200 mm (i.e., 1200 mm in the short direction (TD)) was obtained as a roll-shaped long body. [Examples 2-3] Except for changing Dispersion Liquid 1 to Dispersion Liquid 2 or Dispersion Liquid 3, the same procedure as in Example 1 was repeated to obtain long resin layer-coated copper foils 2 and 3 in the form of a roll.
[0060] 4. Evaluation of resin-coated metal foil The long resin-coated copper foil 1 was divided in the short direction (TD) of the resin layer at 200 mm intervals, and the endmost divided parts were set as the TD end parts, and the central divided part was set as the TD central part, and samples were cut out from each. Using a laser microscope (Keyence Corporation's shape analysis laser microscope "VK-X150"), the root mean square height Rq value and the ten-point average roughness Rz value at the center of the surface of the resin layer of each sample on the side not in contact with the metal foil were measured in accordance with JIS B 0601-2001 (line roughness). jis The values were measured. As a result, the Rq value of the end portion in the TD direction (end portion Rq value) and the Rq value of the center portion in the TD direction (center portion Rq value) were both less than 0.5 μm, and the ratio of the end portion Rq value to the center portion Rq value was 1.12. In addition, Rz at the TD end jis Value (end Rz jis value) and Rz at the center in the TD direction jis Value (center Rz jis The Rz value is less than 1.5 μm and the center Rz jis Edge Rz for value jis The ratio of values was 1.20.
[0061] For the long resin-coated copper foil 2 and the long resin-coated copper foil 3, samples were cut out from the end portion in the TD direction and the center portion in the TD direction in the same manner as described above, and the root mean square height Rq value and the ten-point average roughness Rz value at the center portion of the surface of the resin layer on the side not in contact with the metal foil in each sample were measured. jis The values were measured. As a result, in the long resin-coated copper foil 2, both the end Rq value and the central Rq value were less than 0.5 μm, but the ratio of the end Rq value to the central Rq value exceeded 1.5. jis Value and central Rz jis All values were less than 1.5 μm, but the central Rz jis Edge Rz for value jis The ratio of values was greater than 1.5. In the long resin-coated copper foil 3, the end Rq value and the central Rq value both exceeded 0.5 μm. jis Value and central Rz jis All values exceeded 1.5 μm.
[0062] The degree of wrinkles generated after winding and unwinding from the roll was least in the order of resin-coated copper foil 1, resin-coated copper foil 2, and resin-coated copper foil 3. In addition, the interlayer adhesion of the resin layer-coated copper foil 1 tends to be higher than the interlayer adhesion of the resin layer-coated copper foil 2 and the resin layer-coated copper foil 3, and the transmission loss at a frequency of 40 GHz of the printed wiring board obtained from the resin layer-coated copper foil 1 tends to be lower than that of the resin layer-coated copper foil 2. [Industrial Applicability]
[0063] The long resin-coated metal foil of the present invention exhibits the physical properties of the F polymer to a high degree, has excellent adhesion to the base layer, and is easy to handle when rolled, with less wrinkling and warping, making it suitable for use in printed wiring boards and the like.
Claims
1. A long resin-layered metal foil having, in this order, a metal foil and a resin layer containing a molten sintered body of particles of a tetrafluoroethylene-based polymer, wherein the ratio of the thickness of the resin layer to the overall thickness of the long resin-layered metal foil is less than 50%, and when the resin layer is divided in a short direction (TD) at intervals of 200 mm, the root-mean-square height Rq value (end Rq value) of the TD end and the root-mean-square height Rq value (center Rq value) of the TD center on the surface of the resin layer not in contact with the metal foil are each less than 0.5 μm, and the ratio of the end Rq value to the center Rq value is in the range of 1±0.
5.
2. The ten-point average roughness Rz of the end portion in the TD direction of the surface of the resin layer not in contact with the metal foil jis Value (end Rz jis value), and the ten-point average roughness Rz jis Value (center Rz jis value) is less than 1.5 μm, and the central Rz jis End Rz value jis The long resin-layered metal foil according to claim 1 , wherein the ratio of the values is in the range of 1±0.
5.
3. The tetrafluoroethylene-based polymer contains, in this order, more than 97.5 mol % and less than 99.5 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), and the carbonyl group-containing group is 1×10 6 or a polymer having 100 or more per unit, or a polymer containing 90 mol % or more but less than 97.5 mol % and more than 2.5 mol % but not more than 10 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), respectively, in that order, and the number of carbonyl group-containing groups is 1×10 6 The long resin-layered metal foil according to claim 1 , wherein the polymer has less than 100 particles per particle.
4. The long resin-layered metal foil according to claim 1, wherein the ratio of the thickness of the resin layer to the total thickness of the long resin-layered metal foil is 35 to 48%.
5. The long resin layer-attached metal foil according to claim 1, wherein the metal foil has a thickness of 5 μm or more and 50 μm or less.
6. 6. The method for producing a long resin-layered metal foil according to claim 1, further comprising: coating a metal foil with a dispersion liquid containing 100 parts by mass of tetrafluoroethylene-based polymer particles having an average particle size of 1 μm or more and less than 10 μm and 80 to 300 parts by mass of water, the dispersion liquid having a particle concentration of 5 to 100 particles / ml having a particle size of 20 to 80 μm as measured by a particle counter, forming a coating layer made of the dispersion liquid on the surface of the metal foil, and heating the metal foil having the coating layer to form a resin layer containing a molten sintered body of the tetrafluoroethylene-based polymer on the surface of the metal foil.
7. The method according to claim 6 , wherein the content of the tetrafluoroethylene-based polymer particles is 30% by mass or more.
8. The method according to claim 6, wherein the dispersion further comprises 5 to 20 parts by mass of a water-soluble solvent having a surface tension of 20 to 30 mN / m.
9. A long resin-layered metal foil having, in this order, a metal foil and a resin layer containing a molten sintered body of particles of a tetrafluoroethylene-based polymer, wherein the ratio of the thickness of the resin layer to the thickness of the entire long resin-layered metal foil is less than 50%, and when the resin layer is divided in a short direction (TD) at intervals of 200 mm, the most extreme divided parts are the TD end parts and the central divided part is the TD central part, the ten-point average roughness Rz of the TD end parts of the surface of the resin layer on the side not in contact with the metal foil is 100 mm. jis Value (end Rz jis value), and Rz jis Value (center Rz jis value) is less than 1.5 μm, and the central Rz jis End Rz value jis A long resin-layered metal foil having a width of 1000 mm or more, in which the ratio of the values is within the range of 1±0.
5.
10. The tetrafluoroethylene-based polymer contains, in this order, more than 97.5 mol % and less than 99.5 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), and the carbonyl group-containing group is 1×10 6 or a polymer having 100 or more per unit, or a polymer containing 90 mol % or more but less than 97.5 mol % and more than 2.5 mol % but not more than 10 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), respectively, in that order, and the number of carbonyl group-containing groups is 1×10 6 The long resin-layered metal foil according to claim 9 , wherein the polymer has less than 100 particles per particle.
11. The long resin-layered metal foil according to claim 9, wherein the ratio of the thickness of the resin layer to the total thickness of the resin-layered metal foil is 35 to 48%.
12. The long resin layer-attached metal foil according to claim 9, wherein the metal foil has a thickness of 5 μm or more and 50 μm or less.
13. 13. The method for producing a long resin-layered metal foil according to claim 9, further comprising: coating a metal foil with a dispersion liquid containing 100 parts by mass of tetrafluoroethylene-based polymer particles having an average particle size of 1 μm or more and less than 10 μm and 80 to 300 parts by mass of water, the dispersion liquid having a particle concentration of 5 to 100 particles / ml having a particle size of 20 to 80 μm as measured by a particle counter, forming a coating layer made of the dispersion liquid on the surface of the metal foil, and heating the metal foil having the coating layer to form a resin layer containing a molten sintered body of the tetrafluoroethylene-based polymer on the surface of the metal foil.
14. The method according to claim 13, wherein the content of the tetrafluoroethylene-based polymer particles is 30% by mass or more.
15. The method according to claim 14, wherein the dispersion further comprises 5 to 20 parts by mass of a water-soluble solvent having a surface tension of 20 to 30 mN / m.
Citation Information
Patent Citations
Substrate for printed wiring board and method for manufacturing same, printed wiring board and method for manufacturing same, and resin base material
WO2016104420A1
Laminate having resin layer and metal layer and production method for same
WO2023032958A1